Influência do calor sobre a máxima fase estável do lactato, concentração fixa de 4mM e limiar anaeróbio individual - Cristiano Lino Monteiro de Barros (2007)
Maximal lactate steady state (MLSS) is considered by some authors as the goldstandard of endurance capacity. It is well established that the blood lactateconcentration (BLC) is higher in exercise performed in the heat and although themechanism responsible for this response is not clear, some authors point out thathigher blood adrenaline concentration may be the main cause. The MLSS has beenwidely studied in various experimental situations. However, the influence of ambienttemperature on MLSS has not been established yet. Thus, the purpuse of this studywas to verify the influence of heat on MLSS and MLSS intensity (MLSSw). Nineyoung male physical education students (24.2 ± 2.5 years; 74.99 ± 7.40 kg; 178.7 ±4.0 cm; 48.07 ± 4.63 mLkg-1min-1) volunteered for the study. MLSS was determinedon a cycle ergometer, inside of an environmental chamber in two experimentalsituations: hot (dry bulb temperature 40°C; MFEL-40) and temperate (dry bulbtemperature 22°C; MFEL-22), both with a relative humidity of 50%. In eachexperimental situation, the subjects performed a graded exercise test (P22ºC e P40ºC)and three to five submaximal tests (Tsub). Both the P22ºC and the P40ºC started with apower output of 60W and had increments of 15W every three minutes. The Tsub were30min long, and the first load was the intensity corresponding to 3,5mM of lactatedetermined in the graded exercise tests. The following intensities were adjustedaccording to the result of the first Tsub. The MLSS was determined as the highestintensity maintained in which the BLC did not increase more than 1mM betweenminutes 10 and 30 of exercise. MLSS-22 was higher than MLSS-40 (5.60 ± 0.26 e4.22 ± 0.48 mM, respectively; p<0.05) and no significant correlation was foundbetween MLSS-22 and MLSS-40 (r= 0.13). The MLSSw was higher in the temperatewhen compared to the hot environment (180 ± 32 e 148 ± 33W, respectively;p<0.05). The MLSSw-22 presented a high correlation with MLSS-40 (r=0.80, p<0.05).The results show that a higher lactate accumulation in the heat reduces the MLSSwand that adjustments in the training load should be done when the MLSS is used asthe criteria to determine the intensity of training sessions.